Uncovering Metalanguage in Grammar Exam and Its Implication on Students' Cognition - Muhammad Dhika Arif Rizqan; Dewi Wardah Mazidatur Rohmah (Lingua, 2020)
As language scholars, have you heard the word ‘metalanguage’? and how about the effect of using metalanguage? The current study aimed to investigate the categories of metalanguage in grammar exam. A total of 17 master students in TEFL were voluntarily recruited as the subjects. Their exams were analyzed in detail to collect the data. The researchers conducted a qualitative inquiry called content analysis. The result exposed that the students produced two categories of metalanguage namely technical and non-technical metalanguage. Based on its frequency, technical metalanguage was produced much more frequently than non-technical metalanguage. Both categories of metalanguage affected students’ cognition. However, technical metalanguage ‘drained’ their cognition a lot more while they were not aware about it.